Designing for sustainability: exploring the intersection of creative arts in digital sustainable ecology by interactive animation / Zhao Jie ... [et al.] - Zhao, Jie; Dalal, Sanghamitra; Abu Bakar, Mohd Syuhaidi; Wan Yahaya, Wan Aida (Universiti Teknologi MARA, Perak, 2024)
This article presents doctoral research examining the intersection of creative arts and sustainable development, focusing on interactive animation in the digital sustainable ecology. The research problem addressed is the sustainability of cultural creativity within the realm of digital media ecology, expanding the traditional understanding of ecological sustainability. The study objective aims to investigate the interplay between interactive animation, sustainable development, and digital cultural communication, exploring potential approaches for designing sustainability within interactive animation. The methodology involves drawing upon media ecology theory, conducting content analysis, and performing a comprehensive literature review and case study analysis. Findings indicate that interactive animation expresses frontage scientific concepts through artistic language, promoting cultural reflection and humanistic communication in the digital ecological environment. Interactive animation facilitates the collection of objective behavioural data, integrating scientific concepts into creative design and iterative research for sustainability. The research highlights the significance of creative arts in addressing challenges and opportunities associated with sustainable technology advancement. Exploring the intersection of creative arts and sustainable development via interactive animation, the study deepens participants' understanding of the art form which engages them in the realms of art and science. Implications include fostering cultural spectacle, promoting humanistic meditation, and integrating scientific concepts into creative design, ultimately contributing to sustainability in the digital ecological environment. Contributions involve providing insights into the potential of interactive animation as an academic research tool, expanding ecological sustainability understanding, and emphasizing the role of creative arts in advancing sustainable technology.